Staurosporine: new lease of life for parent compound of today's novel and highly successful anti-cancer drugs. (August 2018) - Ōmura, Satoshi; Asami, Yukihiro; Crump, Andy
Abstract Staurosporine, together with such examples as penicillin, aspirin, ivermectin and sildenafil, exemplifies the role that serendipity has in drug discovery and why 'finding things without actually searching for them' retains a prominent role in drug discovery. Hitherto not clinically useful, due to its potency and promiscuity, new delivery technology is opening up new horizons for what was previously just the parent compound of innovative, highly-successful anti-cancer agents.